A Comprehensive Review of the Fate of Pathogens during Vermicomposting of Organic Wastes. Issue 1 (1st January 2018) - Swati, Ankita; Hait, Subrata
Abstract : Management of both municipal and industrial organic wastes remains a major threat to biota and the environment due to the presence of pathogens in abundance. Vermicomposting employing earthworms is increasingly gaining attention as a sustainable and ecofriendly technique to transform and sanitize a variety of organic wastes into nutrient‐rich biofertilizer. Although considerable research has been undertaken to show that vermicomposting can significantly reduce pathogenic contents, there is little effort to summarize the various mechanisms responsible for it. With the aim to assess the fate of pathogens during vermicomposting of various organic wastes, this article provides a comprehensive summary on the occurrence of pathogens in a variety of wastes vis‐à‐vis pathogens standards, the efficacy of the process for pathogen reduction, and current knowledge of the plausible mechanisms involved. It is evident from the present study that earthworms and endosymbiotic microbes during vermicomposting tend to eliminate pathogens by enhancing enzymatic activities in both gut‐ and cast‐associated processes. Pathogen reduction during vermicomposting can be plausibly attributed to direct actions like microbial inhibition due to intestinal enzymatic action, and secretion of coelomic fluids with antibacterial properties, as well as indirect actions like stimulation of endemic microbes leading to competition and antagonism, and aeration by burrowing activity. Further, the pathogen reduction during vermicomposting is largely selective, and earthworms exert a differential effect according to the earthworm species and whether the pathogen considered is Gram‐positive or ‐negative, owing to its cell wall composition. However, further research is necessary to understand the exact mechanisms involved for pathogen reduction during vermistabilization of municipal and industrial organic wastes. Core Ideas: Vermicomposting using earthworms effectively sanitizes various organic wastes. Pathogen removal during this process is linked to direct and indirect earthworm actions. Pathogen reduction during vermicomposting is largely selective. Earthworms differentially affect pathogens, depending on bacteria being either G+ or G −.